Sustainability of dairy farming in Colombia’s High Andean region - Durana, Claudia; Murgueitio, Enrique; Murgueitio, Bernardo (Frontiers in Sustainable Food Systems, 2023)
Bovine livestock covers more than a third of the earth’s surface and has transformed various natural ecosystems in different parts of the world, including those in fragile, biodiverse regions. Such livestock is found in several of these ecosystems throughout Colombia, and face productivity limitations and environmental impacts. One of them, the High Andean region represents a strategic ecosystem for the conservation of biodiversity globally. Dairy farming in this area has undeniable socioeconomic relevance that is currently threatened by climate variability and market globalization. In this article we explore key elements for the sustainability of dairy livestock in the High Andean region, considering environmental conditions, technical and economic viability, as well as its relationship with society’s values and objectives. Through applied research, field trials, participant observation, consultation with experts, and bibliographic review, we analyze the factors that hinder dairy farming in the High Andean region. We conclude that the traditional models-extensive and conventional intensification-present economic problems, generate environmental impacts and are vulnerable to current changes in the social and environmental plains. We propose to venture into different approaches and technologies, such as agroecological production with silvopastoral systems.